2011
DOI: 10.1002/humu.21544
|View full text |Cite
|
Sign up to set email alerts
|

A cis-acting regulatory variation of the estrogen receptor α (ESR1) gene is associated with hepatitis B virus-related liver cirrhosis

Abstract: The hepatic fibrogenesis and sexual dimorphism of hepatitis B virus-related liver cirrhosis (HBV-LC) are related to estrogen and its receptors. Abnormal expression of estrogen receptor α (ESR1) is implicated in the development of cirrhosis in both animal models and humans. Here, we examine whether the ESR1 polymorphisms are related to HBV-LC risk among chronic HBV carriers, and we investigate the functional significance of positively associated polymorphisms. A total of 2,404 unrelated Chinese HBV carriers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Mice were fed a control or a 1% (wt/wt) cholic acid (CA) diet for 7 days. liver (13,28), may preferentially modulate HBV transcription and replication in males, possibly contributing to the greater disease burden associated with chronic HBV infection in men than in women (21,27,60).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were fed a control or a 1% (wt/wt) cholic acid (CA) diet for 7 days. liver (13,28), may preferentially modulate HBV transcription and replication in males, possibly contributing to the greater disease burden associated with chronic HBV infection in men than in women (21,27,60).…”
Section: Resultsmentioning
confidence: 99%
“…1) (13, 28). The reasons for these differences are currently unclear, but it is worth noting that disease progression is generally more severe in males than in females, indicating that there are sexually dimorphic differences present in both mice and humans (21,27,60).…”
Section: Discussionmentioning
confidence: 99%
“…ER-a mediated oestrogen plays a major biological function in the liver. Clinical and animal-based experiments have demonstrated that abnormal ER-a expression is closely related to hepatocyte proliferation and liver cirrhosis (Shimizu, 2003;Yan et al, 2011). For instance, HBV X protein can inhibit ER transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Additional 334 HBV carriers with severe CHB (S-CHB) flare were also enrolled and used as controls for the reactivation of hepatitis B. Five hundred and ten patients with LC with acute or chronic decompensation but without ACLF were used as LC controls, who were from our previous study 17. All participants were positive for HBV surface antigen at least 12 months, and had no serological evidence for coinfection or superinfection with HCV, hepatitis D virus and HIV.…”
Section: Methodsmentioning
confidence: 99%